Pb-substituted hydroxyapatite catalysts prepared by coprecipitation method for oxidative coupling of methane - Lee, KY; Han, YC; Suh, DJ; Park, TJ (ELSEVIER SCIENCE PUBL B V, 1998)
Pb-substituted hydroxyapatites (Ca(10-x)Pb-x(PO4)(6)(OH)(2), x=0-10) prepared by coprecipitation method were studied as catalysts for oxidative coupling of methane using gas flow reactor in the temperature range of 675 to 800 degrees C. They showed much higher activity for the production of C-2 compounds than those of unsubstituted hydroxyapatites. Especially, Ca9.5Pb0.5(PO4)(6)(OH)(2) showed the highest activity among them, which revealed maximum C-2 yield of about 22%. As compared to the catalysts prepared by ion-exchange method, these catalysts had much higher activity and better thermal stability. Such high activity and stability of the catalysts could be confirmed by XPS, XRD, ICP, etc. to be resulted from the optimum amount of Pb substitution, uniformity of structure, and the maintenance of their own structure during the reaction.
Keywords: LEAD